2007
DOI: 10.1001/archotol.133.10.1013
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Screening for Synchronous Thyroid Disease in Patients Presenting With Primary Hyperparathyroidism

Abstract: To use decision analysis to compare the costs associated with minimally invasive parathyroidectomy (MIP) and bilateral neck exploration (BNE) in patients with primary hyperparathyroidism with regard to treatment of incidental synchronous thyroid disease. Design: We developed a decision tree model to evaluate the cost of managing thyroid pathology in primary hyperparathyroidism with the following 3 approaches: MIP, MIP with preoperative ultrasonography, and routine BNE with intraoperative thyroid evaluation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…8,12,13,14,15 More recent published studies report the coexistence of non-medullary thyroid cancer in 2-18% of patients operated on for pHPT. 5,8,16,17,18 Strichartz and Giuliano conducted a retrospective review of 308 patients who underwent an operation for hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,12,13,14,15 More recent published studies report the coexistence of non-medullary thyroid cancer in 2-18% of patients operated on for pHPT. 5,8,16,17,18 Strichartz and Giuliano conducted a retrospective review of 308 patients who underwent an operation for hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to be a cost-effective undertaking when utilized in conjunction with MIPS. 13 With these points in mind, the debate about the nature and extent of treatment for isolated well-differentiated thyroid carcinoma is entertained in an entirely different context when considered in combination with pHPT requiring surgical treatment. In line with national endocrine disease treatment center practice patterns, our adoption of MIPS for pHPT attributable to a localizing adenoma precludes exploration of the entire neck and careful examination of the thyroid gland at time of operation.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also shown that the use of ultrasound in conjunction with MIPS is not a cost prohibitive endeavor [19]. With these points in mind, the debate about the nature and extent of treatment for isolated papillary thyroid microcarcinoma takes on a different perspective when discussed in combination with pHPT requiring surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Combining ultrasound with MIBI was also noted by Arciero et al to be cost‐effective when combined with minimally invasive parathyroidectomy. Furthermore, 2 recent cost analyses supported combined imaging for localization, as this decreased the rate of conversion to bilateral neck exploration, and was the most cost‐effective option overall …”
Section: Discussionmentioning
confidence: 95%